Utilization of whole microalgal biomass for advanced biofuel and biorefinery applications. (May 2022) - Moon, Myounghoon; Park, Won-Kun; Lee, Soo Youn; Hwang, Kyung-Ran; Lee, Sangmin; Kim, Min-Sik; Kim, Bolam; Oh, You-Kwan; Lee, Jin-Suk
Abstract: To address issues related to climate crises, microalgae-based biofuels are considered a promising option for reducing carbon dioxide emissions in the transportation sector. However, despite extensive research conducted over the past 20 years, there are major limitations in the application of conventional algal biodiesel, such as the instability of oxygen-containing fuel, blending wall limitations (less than 20%), and poor cost competitiveness. Recently, biomass-based renewable hydrocarbon fuels (drop-in biofuels) have been considered technologically competitive alternatives to petrofuels owing to the advantages of carbon dioxide reduction, high energy density, and compatibility with existing infrastructure. This review discusses the integrative utilization of whole algal biomass for the development of an advanced algal biorefinery process that could strategically help produce drop-in biofuels and multiple by-products to meet the growing fuel demand and secure economic feasibility. This review provides an updated overview of recent technical advancements in the (1) mass cultivation of oleaginous algal biomass obtained from industrial wastes, (2) production of renewable biodiesel and bio-jet fuel using algal lipids via catalytic upgrading, and (3) diversification of bio-products generated from residual lipid-extracted biomass, such as hydrogen, methane, alcohols, bio-oils, organic acids, biosorbents, biomaterials, and nutrients. The challenges and prospects for practical application are discussed along with the major constraints on the commercialization of integrative algal biorefining. Graphical abstract: Image 1 Highlights: Integrative utilization of whole biomass is required for economic algal biorefining. Mass cultivation of lipid-rich algal biomass using CO2 -rich flue gas and wastewater. Catalytic upgrading of renewable diesel and bio-jet fuel from algal neutral lipids. Diversification of products from lipid-extracted biomass via subsequent conversions.